PELATIHAN GURU DALAM PENGGUNAAN VIDIO PEMBELAJARAN DI PAUD/TK HATINIA BAROKAH SUKARAMAI LABUHANBATU UTARA - dkk., Mursal Aziz (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to describe how the implementation of teacher training conducted by STIT Al-Ittihadiyah Labuhanbatu Utara for PAUD / TK Hatinia Barokah teachers, then how the benefits of teacher training carried out by STIT Al-Ittihadiyah Labuhanbatu Utara. This research is a field research (field research) with a qualitative approach and the data collection techniques are observation, interview, action and documentation. The results of this study indicate that the implementation of teacher training conducted by STIT Al-Ittihadiyah Labuhanbatu Utara for PAUD / TK Hatinia Barokah teachers is a community service program on making audio-visual media, especially designing and making learning videos. The benefits of teacher training teacher training activities carried out by STIT Al-Ittihadiyah Labuhanbatu Utara are to improve the ability of teachers to create and use video media in learning, especially during the Covid 19 pandemic.